Diagnostic utility of bone marrow examination for the assessment of patients with fever of unknown origin: a 10‐year single‐centre experience. Issue 6 (June 2014) - Labrador, J.; Pérez‐López, E.; Martín, A.; Cabrero, M.; Puig, N.; Díez‐Campelo, M.
Abstract Bone marrow (BM) examination is included in the diagnostic algorithm of fever of unknown origin (FUO), although its role is not clearly determined. The purpose of this study was to assess the role of BM studies in patients with FUO. We retrospectively reviewed 45 consecutive patients (25% human immunodeficiency virus‐positive) with FUO who underwent a BM study in the University Hospital of Salamanca from 2000 to 2010. We analysed the diagnostic role of BM smears, multiparameter flow cytometry analysis, histology and microbiological cultures. Five patients (11%) were finally diagnosed by BM study (three had an infectious disease and two were found to have haematological malignancies), all of whom were immunocompetent patients. Histology was the most useful study (diagnosis was obtained in 4/5 patients), while BM cultures did not establish the final diagnosis in any patient. Flow cytometry established the diagnosis in one patient, although this patient was also diagnosed by histology. In conclusion, BM study is useful for establishing the aetiology of FUO. BM biopsy for histological examination should be always mandatory if a BM examination is performed.